CODE SWITCHING BY TEACHERS IN ENGLISH CLASS AT SMA MUHAMMADIYAH 1 PONOROGO IN ACADEMIC YEAR 2018/2019 - Rizqi Fajrin Ramadhani; Niken Reti Indriastuti; Diyah Atiek Mustikawati (EDUPEDIA, 2019)
The aims of this research were identify: 1) The types of code switching, 2) Find out the factors influence the teachers to switch English into Indonesian or the opposite, 3) Analyze the impact of teacher’s code switching for the students. This research was held on SMA Muhammadiyah 1 Ponorogo. The research design was qualitative research especially case study. Research used observation and interview as the data collection technique in this research. To analyze the data the writer transcribing interviewing, scanning material, typing up field notes, coding process, making qualitative narrative, and making interpretation the data. Based on finding, the types of code switching which was used by English teacher at SMA Muhammadiyah 1 Ponorogo include tag code switching, inter sentential code switching, and intra sentential code switching with different quantities. The factor influence teachers to conducted switch English to Indonesian such as the students understanding was the big factor and the students characteristic were different, they had not same ability in English. Finally, the researcher proposed suggestion to the teachers to maintain using code switching during teaching and learning English in classroom, but continue to prioritize English as the primary. They could switch Bahasa Indonesia, but when used for certain purposes only.